Fortifikasi Ekstrak Filamen Telur Ikan Terbang (Hirundichthys oxicheplus) dalam Saus Cabai - Rahmawati Saleh; Luthfiah Luthfiah; Adilham Adilham; Andi Santi; Rahmat Tola (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
Flying fish (Hirundichthys oxycephlus) roe filaments, which are often considered as by-products, have high protein content and various essential nutrients, thus potentially increasing the nutritional value of food products. With innovation and in-depth research, this waste can be transformed into products with economic value while supporting the implementation of sustainability principles in the fisheries industry, in this case sauce as a flavoring that has become an important part of the food industry. This study aims to determine the quality of the texture and taste of chili sauce fortified with fly fish (Hirundichthys oxycephlus) roe filament extract and to determine the protein content and water content of chili sauce enriched with fly fish (Hirundichthys oxycephlus) roe filament extract. The methodology used in this study was Complete Random Design (CRD) with variations in filament powder concentration (0%, 0.5%, 1%, and 1.5%) on the sensory characteristics of chili sauce, which include aroma, color, taste, and texture. The results of organoleptic tests showed that the addition of fly fish (Hirundichthys oxycephlus) egg filament extract had a significant positive impact on all sensory parameters tested. The average aroma score increased from 2.88 in the non-enriched treatment to 3.90 at the highest filament powder concentration (1.5%). In addition, the taste score also showed the most striking increase, from 2.80 to 4.33. Analysis of the water content of the chili sauce product was recorded at 79.93% according to (SNI 01-2976-2006), while the protein content reached 10.53%, indicating the potential of this product as an additional source of protein in daily consumption patterns.